ENHANCING MARKETING AND MANAGEMENT CAPABILITIES IN THE STRATEGIC DEVELOPMENT OF THE SERVICE SECTOR IN NUKUS CITY FOR SUSTAINABLE ECONOMIC GROWTH AND IMPROVEMENT OF POPULATION WELFARE - Sarsenbaev Bakhitjan Abdulgazievich; Kengesov Diyorbek Umidovich; Nurniyazova Dilnoza Arzubay qizi; Khalmuratova Dilnaz Suleyman qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This study examines the strategic development of the service sector in Nukus  city  and  the  broader  Republic  of  Karakalpakstan  from  2017  to  2024,  with particular  attention  to  improving  marketing  and  management  capabilities  as mechanisms for ensuring sustainable economic growth and enhancing the well-being of the population. Based on statistical data analysis, the research reveals a consistent upward trend in service provision, led by sectors such as financial services, transport, and  information  technologies.  The  study  underscores  the  imperative  of  integrating modern marketing strategies and effective management systems to harness the region’s untapped  economic  potential.  Conclusions  and  recommendations  are  presented  to inform regional development policies.